Strategi Pembelajaran pada Kemampuan Membaca Pemahaman Siswa Sekolah Dasar Negeri 3 Jabalsari - Nadella Neno Christian Dharu; Hikmah Eva Trisnantari (Arus Jurnal Pendidikan, 2022)
Learning strategy is a plan, method, or series of activities made to achieve certain educational goals, as well as reading comprehension. Reading comprehension ability itself is defined as an activity to build or reconstruct the message or meaning contained in the reading by involving the knowledge already possessed so that it can understand the main idea, some important details and or the overall content of the reading. Based on the results of initial observations, it is known that Grades IV and V students have good reading comprehension skills. So that researchers describe it in a study. This research was conducted to find out about lesson planning on reading comprehension skills at State Elementary School 3 Jabalsari Kec. Sumbergempol Kab. Tulungagung and learning methods on reading comprehension skills at State Elementary School 3 Jabalsari Kec. Sumbergempol Kab. Tulungagung. This research is a qualitative research with the type of case study research. The subjects of this study were Class IV and V teachers. From research activities, it can be seen that learning planning on reading comprehension, namely the preparation of lesson plans is not specific for reading comprehension, but includes reading comprehension points and learning objectives with cognitive domains and developing student-centered teaching and learning activities. Then the learning method on reading comprehension skills is by encouraging student participation to be active by directing students to group and classical discussions and by motivating students to think at higher levels through question and answer activities and discussions where students are emphasized to express opinions or argue about the results after processing reading